Appeal for cultural equity - Lomax, Alan (International Library of African Music, 1980)
Man has a more indirect relation to nature than most other animals because his environmental tie is normally mediated by a cultural system. Since human adaptation has been largely cultural rather than biological, human sub-species are rather the product of shifts in learned culture patterns than in genetically inherited traits. It is the flexibility of these culture patterns — composed of technique, social organization, and communication — that has enabled the human species to flourish in every zone of the planet.
Keywords: African Music